Hybrid Repair of a Persistent Sciatic Artery Aneurysm. (November 2022) - de Boer, Madeleine; Joseph, Simon; Shiraev, Timothy; Boyle, Richard; Dubenec, Steven
Persistent sciatic arteries are rare congenital abnormalities, with an incidence between .01-.6%. Whilst most patients with the pathology are asymptomatic during their younger years, up to 48% of patients will suffer aneurysmal degeneration of the persistent sciatic artery and present with claudication or lower limb ischaemia (from distal embolisation of mural thrombus). Due to the rare nature of persistent sciatic artery aneurysms, optimal management of the pathology is yet to be determined. Both endovascular and open techniques have been described in the management of this pathology, however hybrid management approaches are reported infrequently. The authors present a case of a persistent sciatic artery aneurysm successfully treated in a 69-year-old male utilising a hybrid approach with a femoropopliteal bypass (below knee), Amplatzer plug occlusion of the aneurysm and subsequent resection of the aneurysm.